Stress Management in Employees of Recently Merged Banks in India - Naik , Banoth Sai Kiran (International Journal of Psychosocial Rehabilitation, 2020)
Stress causes because of numerous factors at work place, which cannot be ignored. Employees try to manage the stress during the course of the work because of severe consequences. Merger is a combination of different businesses in the market, which means different business cultures to be gathered and functioned as a single entity in order to get gains, opportunities and strengthen themselves. In fact different business cultures create inconvenience to the crew of the organization, which leads to stressful environment. Stress decreases the productivity and makes them feel unsecure at the workplaces. Research is aimed to study the stress factors post- merger and the techniques used to manage stress of recently merged Banking Companies in India.